(untitled) (Research, Society and Development, 2024)
Objective: To identify the clinical practice of Brazilian nurses in the management of Malignant Neoplastic Wounds (MNW). Method: A cross-sectional descriptive study with a quantitative approach, using a survey type. Data collection took place from June to November 2023, divided into two stages. The first involved the construction and validation of an instrument to assess nurses’ clinical practice regarding MNW, using the online Delphi Technique with a committee of experts. The second stage consisted of applying this instrument to Brazilian nurses with experience in MNW, recruited using the snowball methodology. Data were collected online via the REDCap platform, ensuring security and efficiency. Data analysis used the Content Validity Index in the first stage and unsupervised machine learning, correspondence analysis, to evaluate associations in the second stage. Results: 201 nurses from various Brazilian states participated, covering all regions. Most were under 30 years old, had between 4 and 7 years of experience, were oncology specialists, identified as female, and resided in the southeast region. There was statistical significance (p ≤ 0.05) in the association of 12 interventions with the nurses’ education or years of experience. Conclusion: Brazilian nurses demonstrate knowledge of general interventions in MNW management, with significant differences in skills for controlling local symptoms, related to practical experience and education level.